In Utero Diagnoses of Strikingly Similar Presentations of Complete Atrioventricular Septal Defects in a Pair of Dizygotic Twins Concordant for Trisomy 21. (17th October 2018) - Ling, Diamond; Dayan, Jonathan G
Abstract : Trisomy 21, or Down syndrome (DS), is a genetic disorder affecting approximately 1 in 500–750 live births. The prevalence of DS has increased over the past two decades, correlating with a rise in the proportion of pregnancies complicated by advanced maternal age. There is also a correlation between advanced maternal age and dizygotic twinning rates. There is an increased risk of at least one twin being affected in dizygotic pregnancies compared to singletons. However, despite this greater relative risk, reports of concordance of DS in both dizygotic twins are very rare. Congenital heart disease (CHD) occurs in roughly 40% of individuals with DS, but there can be considerable phenotypic variation. The most common, atrioventricular septal defect accounts for only 40% of CHD seen in DS. There is also a higher incidence of CHD in twins, but also with a low incidence of concordance. There have been only five reported cases of concordant DS in dizygotic twins with confirmed chromosomal analyses; none of which describe concordant congenital heart disease. Here, we describe an unusual case of dizygotic twins of differing genders concordant for both Down syndrome and congenital heart disease of a strikingly similar presentation.